The role of shear modulus on the mechanical behavior of elastomeric bearings when subjected to combined axial and shear loads. (1st December 2021) - Kalfas, Konstantinos N.; Ghorbani Amirabad, Nooshin; Forcellini, Davide
Highlights: The role of shear modulus, G b, on the mechanical behavior of EB. Closed-form solution describing the non-linear response of EB. A unique element to reproduce the combined axial-shear macroscopic behavior of EB. Abstract: Multi-layered elastomeric bearings (EB) are used extensively in civil structures and infrastructures, due to their ability to mitigate the movements that structures such as buildings, bridges and nuclear power plants may experience when they are subjected to vibrations, earthquakes and other natural hazards. During large movements, EBs may experience both axial and shear loads and consequently displacements which have been investigated in several studies based on analytical, experimental and numerical approaches. This study investigates the role of the shear modulus, Gb, on the mechanical behavior of EBs when combined axial and shear loads are applied, by performing numerical simulations. The main objective is a closed-form solution that describes the non-linear relationship between the vertical axial load, the relative rotation and the shear modulus of the EBs. The presented formulation constitutes a proposal for potential applications to numerical platforms in order to reproduce the combined axial – shear macroscopic behavior of the EBs.